Pengembangan bahan ajar materi bangun ruang sisi datar menggunakan pendekatan saintifik berbantuan geogebra - Hana Gandhi Azizah; Muhammad Ghiyats Ristiana (IKIP Siliwangi, 2023)
This study aims to produce worthwhile and practical teaching materials by using a scientific approach that helps GeoGebra. This research is supported by Sugiyono (2009) model. This study was conducted in one of SMP countries in Bandung Regency, with the subject of two-class research or about 70 students of class VIII in the events of the year of the 2021/2022 school. The material of the material developed is polyhedron. All data is collected from the Lembar Kerja Peserta Didik (LKPD) of GeoGebra, authenticate system validation, questionnaires of validation media, directory of validation practitioners, practitioner's cash response, and student response questionnaire. Before conducting research, researchers first conducted preliminary studies, then designed teaching materials, then tested the feasibility to experts with 81% of the material expert, 82% of media experts, and 93% of practitioners experts with very well-worthy categories. Practical tests are seen from the questionnaire of response teachers with 94% and question response in the 86% result with very practical category.